Description of four new species of Hypaeus Simon and redescription of H. taczanowskii Mello-Leitão (Araneae: Salticidae: Amycinae) - Araújo, Magda H.s.; Ruiz, Gustavo R.s. (Zootaxa, 2015)
Four new species of Hypaeus Simon are described from the Brazilian Amazon, all based on both sexes: H. tridactylus sp. nov. and H. femoratus sp. nov. from Juruti, Pará, and H. poseidon sp. nov. and H. terraemediae sp. nov. from São Félix do Xingu, Pará. Additionally, Asaracus pauciaculeis Caporiacco, 1947 is transferred from Mago O.P.-Cambridge, resulting in Hypaeus pauciaculeis comb. nov. Both sexes of H. taczanowskii (Mello-Leitão, 1948), the type species of Hypaeus, are redescribed for comparisons.